Methylenetetrahydrofolate reductase C677T (Ala>Val, rs1801133 C>T) polymorphism decreases the susceptibility of hepatocellular carcinoma: a meta-analysis involving 12, 628 subjects. Issue 2 (20th February 2020) - Zhang, Sheng; Jiang, Jiakai; Tang, Weifeng; Liu, Longgen
Abstract: C677T (Ala>Val, rs1801133 C>T), a non-synonymous variant of methylenetetrahydrofolate reductase ( MTHFR ) gene, has been found to be associated with an impair enzyme activity of MTHFR. The relationship of MTHFR rs1801133 with hepatocellular carcinoma (HCC) has been extensively investigated. However, the findings were conflicting. Recently, more investigations have been conducted on the relationship of MTHFR rs1801133 with HCC. To obtain a more precise assessment on the effect of this non-synonymous variant to the development of HCC, a pooled-analysis was performed. This meta-analysis consisted of 19 independent case–control studies. By using the odds ratio (OR) combined with 95% confidence interval (CI), the relationship of MTHFR rs1801133 with HCC risk was determined. A total of 19 independent case–control studies were included. Finally, 6, 102 HCC cases and 6, 526 controls were recruited to examine the relationship of MTHFR rs1801133 with HCC risk. In recessive model (TT vs. CC/CT), the findings reached statistical significance (OR, 0.90; 95%CI, 0.82–0.98; P = 0.016). Subgroup analysis also found an association between MTHFR rs1801133 polymorphism and the decreased risk of HCC in hepatitis/virus related patients (recessive model: OR, 0.85; 95%CI, 0.72–0.99; P = 0.035, and allele model: OR, 0.90; 95%CI, 0.81–0.99; P = 0.028). Subgroup analyses indicated that extreme heterogeneity existed in Asian population, larger sample size investigation, hospital-based study and normal/healthy control subgroups. The shape of Begger's seemed symmetrical. Egger's linear regression test also confirmed these evaluations. Sensitivity analyses suggested that our findings were stable. In summary, our results highlight that MTHFR rs1801133 polymorphism decreases HCC susceptibility. The relationship warrants a further assessment.